Measuring some kinesthetic perception tests using the computer-programmed atrussonic distance sensor for volleyball players according to their specialities - Fail, M. R.; Ashoor, R. A.; Oubed, W. A. (Journal of Human Sport & Exercise, 2021)
The problem of the research lies in the possibility of making the tests used through accurate devices that work according to the computer system to avoid self-evaluation, which takes a lot of time in the testing process, the study aimed to design some tests of kinaesthetic perception using the computer-programmed atrousonic distance sensor and identify the level of some kinaesthetic perception tests For the research sample, the research sample was represented by a group of volleyball players in (Basra, Maysan, Dhi Qar), totalling (40) players divided according to their specializations in playing. The results of the Colum grove Seminarov test for the normal distribution of volleyball players according to their specialities as well as the results of the analysis of variance of the value of (F) The calculated and tabular tests for the perception of the distance for the right hand and the perception of the distance for the left hand of the volleyball players, the researchers concluded that there are differences between the specialities of playing in the volleyball team and this is evidence that the specifications of the volleyball players differ from one player to another according to the requirements of modern play. Researching the reasons that cause the variation in the level of some specialities of playing in the volleyball team.